(untitled) (Research, Society and Development, 2023)
Among the existing classes of drugs in a hospital institution, antimicrobials (AMB) are the most prescribed. They are used in the treatment of infectious diseases, decreasing the mortality and morbidity of these diseases. As a reflection, this class is also more prescribed in Intensive Care Units (ICU). The objective of the study was to describe the pattern of antimicrobial consumption in the ICUs of Hospital de Urgências de Goiás Dr. Valdemiro Cruz (HUGO) against the Anatomical Therapeutic Chemical (ATC)/Defined Daily Dose (DDD) methodology, as well as comparing values ​​obtained with DDD values ​​provided by the World Health Organization (WHO), during the February period and March 2022. The consumption of antimicrobials was expressed in DDD per 1000 patients/day. The WHO ATC/DDD classification was used. A total of 196 patients were hospitalized in the Intensive Care Units, among which 58.54% (ICU1), 66.22% (ICU 2), 74.51% (ICU 3) and 65.63% (ICU 4) were male, with a prevalence of elderly patients being 69.09% (ICU 1), 61.36% (ICU 2), 65.76% (ICU 3) and 61.43% (ICU 4). The most consumed antimicrobials were Ceftriaxone, Meropenem, Piperacillin + Tazobactam and Vancomycin. The use of antibiotics and increasing resistance to them in the ICU setting highlights the urgent need for better administration of this class focused on the ICU, with a focus on facilitating the immediate administration of appropriate antimicrobial therapy among patients at risk of infection.